Pendidikan Karakter Sosial Qur'ani: Studi Tafsir Surat Al-Hujurat Ayat 11-13 - Imam Shofwan; Achmad Munib (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
This study explores the values of social character education in Surah Al-Hujurat verses 11-13. This study uses the library research method by utilizing two commentary books classified as works of classical and contemporary interpretation, namely, the interpretation of Ibn Kathir and Al-Azhar. The results of this study found that Al-Hujurat verses 11-13 contain meaning in the form of teachings and social values as the basis for carrying out a humane society. Education and social values are stored in various prohibition states with many positive values. The ban consists of several behaviors not insulting fellow human beings, self-reproach and others, prejudice, spreading false news, looking for other people's faults, and various derived behaviors. Implementing all forms of prohibition has an orientation towards forming individual social character, which is the basis for carrying out social life.